THE INFLUENCE OF INVESTMENT DECISIONS, FINANCING DECISIONS, AND INFLATION ON FIRM VALUE WITH PROFITABILITY AS A MEDIATING VARIABLE IN INDONESIAN INSURANCE COMPANIES - Meice Laura; Lestari Wuryanti; Anita (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of investment decisions, financing decisions, and inflation on firm value, with profitability as a mediating variable in insurance companies listed on the Indonesia Stock Exchange for the 2021–2023 period. This study uses a quantitative approach with panel data regression analysis on 15 insurance companies selected through a purposive sampling method. The results show that investment decisions significantly influence firm value, while financing decisions and inflation do not significantly influence firm value. Simultaneously, investment decisions, financing decisions, and inflation significantly influence firm value. The coefficient of determination indicates that the independent variables are able to explain firm value by 21.27%. The Sobel test results indicate that profitability is unable to mediate the influence of investment decisions, financing decisions, and inflation on firm value. Based on these results, it can be concluded that investment decisions are the main factor influencing insurance company value, while profitability does not play a role as a mediating variable.